2005
DOI: 10.1152/ajpheart.00548.2004
|View full text |Cite
|
Sign up to set email alerts
|

A2Badenosine receptor mediates human chorionic vasoconstriction and signals through arachidonic acid cascade

Abstract: Because adenosine is a vascular tone modulator, we examined the effect of adenosine and congeners in the vascular reactivity of isolated human placental vessels and in perfused cotyledons. We characterized its vasomotor action and tentatively identified the receptor subtypes and their intracellular signaling mechanisms. We recorded isometric tension from the circular layer of chorionic vessel rings maintained under 1.5 g of basal tension or precontracted with KCl. The relative order of potency of adenosine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 49 publications
(61 reference statements)
2
43
1
Order By: Relevance
“…Numerous pharmacological studies demonstrate that the activation of A 2B AR by adenosine triggers proinflammatory effects by upregulating proinflammatory cytokines and growth factors and downregulating anti-inflammatory cytokines in many cell types (Donoso et al, 2005;Feoktistov and Biaggioni, 1995;Fiebich et al, 1996;Rees et al, 2003;Ryzhov et al, 2004;Ryzhov et al, 2008a;Zhong et al, 2004), while there is also some contradictory evidence, depending on the systems and conditions used (Eckle et al, 2008a;Eckle et al, 2008b). Yang and colleagues showed that A 2B AR knockout mice display mild elevation of proinflammatory TNF-a and IL-6, and decreased levels of anti-inflammatory IL-10 in the plasma under basal conditions, and more so under LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pharmacological studies demonstrate that the activation of A 2B AR by adenosine triggers proinflammatory effects by upregulating proinflammatory cytokines and growth factors and downregulating anti-inflammatory cytokines in many cell types (Donoso et al, 2005;Feoktistov and Biaggioni, 1995;Fiebich et al, 1996;Rees et al, 2003;Ryzhov et al, 2004;Ryzhov et al, 2008a;Zhong et al, 2004), while there is also some contradictory evidence, depending on the systems and conditions used (Eckle et al, 2008a;Eckle et al, 2008b). Yang and colleagues showed that A 2B AR knockout mice display mild elevation of proinflammatory TNF-a and IL-6, and decreased levels of anti-inflammatory IL-10 in the plasma under basal conditions, and more so under LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…20), which is not sensitive to cholera or pertussis toxin but is antagonized by the slightly A 2B AR-selective antagonist enprofylline (3-propylxanthine) 20 . The arachidonic acid pathway was also recently demonstrated to be involved in A 2B AR activation 23 .…”
Section: Ar Signalling Pathways and Regulationmentioning
confidence: 99%
“…Activation of the A 2B AR induces vasodilation in some vascular beds 91,92 , such as the main pulmonary artery of guinea pigs, and induces human chorionic vasoconstriction and signals through the arachidonic acid cascade 23 . The A 2B AR is selectively upregulated by hypoxia, and A 2B AR antagonists effectively neutralize ATP-elicited reduction in post-hypoxic endothelial permeability 93 .…”
Section: Vasodilationmentioning
confidence: 99%
“…Adenosine and endothelium-derived NO and prostacyclin are important local mediators of vasodilatation. In several human vascular beds, adenosine A 2 receptors mediate vasodilatation in part through endothelium, possibly by releasing NO (Sobrevia et al, 1997;Li et al, 1998) and prostacyclin (Chiang et al, 1994;Donoso et al, 2005). Other studies, however, failed to demonstrate endothelium-dependent responses in the presence of adenosine (Sabouni et al, 1990;Tsai et al, 1996;Kemp and Cocks, 1999).…”
mentioning
confidence: 99%
“…Other studies, however, failed to demonstrate endothelium-dependent responses in the presence of adenosine (Sabouni et al, 1990;Tsai et al, 1996;Kemp and Cocks, 1999). Controversy also exists on the receptor subtype (A 2A or A 2B ) predominating on endothelial cells (Chiang et al, 1994;Iwamoto et al, 1994;Sobrevia et al, 1997;Li et al, 1998;Donoso et al, 2005). Since little is known about the adenosine receptor present on endothelial cells of HCC and the impairment of endothelium function may be one of the factors for the attenuation of adenosine receptor-mediated responses, we thought it would be interesting to explore adenosine-induced relaxation of HCC smooth muscle in control subjects after inhibiting endothelial production of NO and prostacyclin compared with patients with vasculogenic impotence exhibiting multiple risk factors for endothelial lesion (e.g., type II diabetes, hypercholesterolemia, hypertension, heavy smoking habits).…”
mentioning
confidence: 99%